Optimisation of phenol extraction from wine using layered double hydroxides and technological evaluation of the bioactive‐rich powder. (9th September 2017) - Pagano, Cinzia; Perioli, Luana; Blasi, Francesca; Bastianini, Maria; Chiesi, Claudia; Cossignani, Lina
Summary: The purpose of this study was to extract functional components, such as phenols, from wine under mild conditions and without the use of organic solvents. A dry and alcohol‐free concentrated wine bioactive extract was obtained using layered double hydroxides (LDHs). The influence of some factors (LDH type, temperature, time and LDH/wine ratio) was evaluated using an experimental design software. Three responses were selected (phenol, anthocyanin and catechin contents). Using the optimised results, the best extraction conditions were as follows: pH 3.7, time 240 min, ratio 3, temperature 20 °C. The sample prepared in these conditions was characterised technologically (size, flowability, wettability) to investigate its manageability and workability. The phenol extract obtained using MgAl‐LDH had suitable particle size and good flowability. A formulation of concentrated wine phenol extract with interesting applications for the nutraceutical field was successfully produced. Abstract : A formulation of concentrated wine phenol extract was obtained using layered double hydroxides (LDH) under mild and solvent‐free conditions, without modifying the pH of the wine. The optimal conditions were studied using response surface methodology.